Queue management in distributed infocommunication systems with service oriented arhitecture - Kovalenko, T. N. (Вебер, 2013)
In this work a mathematical model of active queue management in a system with Service Oriented Architecture (SOA) according to a Random Early Detection algorithm is presen-ted. Analysis of the algorithm efficiency for overload prevention in SOA systems is done. Influence on the system performance of such algorithm’s parameters as mark probability denominator, minimal and maximal threshold values of queue length is studied. Recommendations on selection of the values of algorithm’s parameters to increase the efficiency of overload prevention in distributed infocommunication SOA systems are formulated. В работе представленa математическая модель активного управления очередями в системе c сервис- ориентированной архитектурой (Service Oriented Architecture, SOA) в соответствии с алгоритмом произвольного раннего обна- ружения (Random Early Detection, RED). Проведен анализ эффективности данного алгоритма для предотвращения перегрузок в системах SOA. Исследовано влияние на работу алгоритма таких его параметров как показа-тель граничной вероятности, минимальное и максимальное пороговые значения длины очереди. Сформулированы рекомендации по выбору значений указных параметров для повышения эффективности борьбы с перегруз-ками в распределенных инфокоммуникационных системах SOA.
Keywords: Service Oriented Architecture; telecommunication systems; infocommunication systems; сервис-ориентированная архитектура; инфокоммуникационные сети